2019
DOI: 10.3390/genes10110899
|View full text |Cite
|
Sign up to set email alerts
|

NOP53 as A Candidate Modifier Locus for Familial Non-Medullary Thyroid Cancer

Abstract: Nonsyndromic familial non-medullary thyroid cancer (FNMTC) represents 3–9% of thyroid cancers, but the susceptibility gene(s) remain unknown. We designed this multicenter study to analyze families with nonsyndromic FNMTC and identify candidate susceptibility genes. We performed exome sequencing of DNA from four affected individuals from one kindred, with five cases of nonsyndromic FNMTC. Single Nucleotide Variants, and insertions and deletions that segregated with all the affected members, were analyzed by San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…NOP53 gene, located in 19q13.33, encodes a nucleolar protein involved in ribosome biogenesis. The germline variant p. Asp31His in NOP53 gene has recently been reported associated with NSFNMTC [ 69 ]. The patients had PTC and Hürthle cell carcinoma in one case, sometimes coexisting with MNG, including toxic MNG in two of the 11 affected members of the three families studied.…”
Section: Non-syndromic Familial Non-medullary Thyroid Carcinoma (Nsfnmentioning
confidence: 99%
See 1 more Smart Citation
“…NOP53 gene, located in 19q13.33, encodes a nucleolar protein involved in ribosome biogenesis. The germline variant p. Asp31His in NOP53 gene has recently been reported associated with NSFNMTC [ 69 ]. The patients had PTC and Hürthle cell carcinoma in one case, sometimes coexisting with MNG, including toxic MNG in two of the 11 affected members of the three families studied.…”
Section: Non-syndromic Familial Non-medullary Thyroid Carcinoma (Nsfnmentioning
confidence: 99%
“…Tumor tissue showed a higher immunohistochemical expression of NOP53 compared to the adjacent normal thyroid tissue in all four cases studied. [ 69 ].…”
Section: Non-syndromic Familial Non-medullary Thyroid Carcinoma (Nsfnmentioning
confidence: 99%
“…This scenario would make it difficult to find a common link among the different affected families. Indeed, part of the families included in this study were included in a previous paper [32], where we suggest that non-syndromic FNMTC may be due to multiple mutations acting as risk alleles and modifier locus for FNMTC, in contrast with most hereditary cancers, in which only 2 or 3 high-penetrance causative genes have been described.…”
Section: Discussionmentioning
confidence: 99%
“…NOP53 participates in ribosome biogenesis and regulates the p53 activation in the case of ribosome biogenesis perturbation. The variant c.91G>C was also identified in three out of 44 families with FNMTC [ 127 ]. In the tumor samples, NOP53 expression was increased when compared to the adjacent normal tissue.…”
Section: Non-syndromic Fnmtcmentioning
confidence: 99%
“…In the tumor samples, NOP53 expression was increased when compared to the adjacent normal tissue. Furthermore, NOP53 knockdown inhibited cell proliferation and colony formation in vitro [ 127 ]. Altogether, these findings suggested that this variant could have an oncogenic role in thyroid tumorigenesis [ 127 ].…”
Section: Non-syndromic Fnmtcmentioning
confidence: 99%